Moodiary: Aplikasi Pencatat Suasana Hati - Ananta, Anggi Diva; Nur, Muhammad Faturrahman; Saputra S., Syawal (Journal of Security, Computer, Information, Embedded, Network, and Intelligence System, 2025)
Moodiary is an Android application developed to help users track their moods and daily activities, aiming to enhance self-awareness and emotional reflection. The app integrates Firebase Authentication for secure login and Firebase Realtime Database for real-time data storage. Featuring a minimalist and user-friendly interface, users can log their daily moods, write short personal narratives, and monitor emotional trends through data visualizations. Moodiary was developed using the Agile methodology, enabling iterative development based on user needs. Key features include icon-based mood tracking, mood history charts, daily reminders, and profile customization. Functional and non-functional testing results show excellent performance in terms of availability, reliability, security, and user experience. Thus, Moodiary serves as an effective digital solution to support mental well-being and self-reflection, particularly for mobile users seeking fast, secure, and personalized emotional tracking tools.